In vitro analysis of colistin-carbapenem combination activity against Acinetobacter spp infection - Micheline Soudeiha; E Salem Sokhn; Ziad Daoud; Dolla Sarkis (Journal of Infection in Developing Countries)
Introduction: Increasing carbapenem resistance in Acinetobacter spp calls for the appraisal of alternative strategies in Acinetobacter spp infection therapy. This study aims at evaluating colistin-carbapenem combination against Acinetobacter spp using the checkerboard, Etest, and time-kill methods.